Trends in Serious Mental Illness in US Assisted Living Compared to Nursing Homes and the Community: 2007-2017 - Hua, Cassandra L. (Am J Geriatr Psychiatry, 2020)
OBJECTIVES: Little is known about the prevalence of serious mental illness (SMI) in assisted living (AL) communities in the United States. Trends in the prevalence of SMI in the AL community were examined over time and in relationship to characteristics such as dual eligibility and health conditions. Within- and between-state variability of SMI in AL was also examined. DESIGN: Samples of Medicare beneficiaries who lived in the 48 contiguous states were created: those who resided in the community, in a nursing home (NH), and in AL on December 31st of each year (2007-2017). We conducted univariate analysis to display the trends in SMI over time in AL compared to NHs and the community. To demonstrate intrastate variability, we examined the prevalence of SMI for each state. We described within-state variability using a Lorenz curve and GINI coefficients. RESULTS. The prevalence of SMI in AL increased by 54%, rising from 7.4% in 2007 to 11.4% in 2017. Residents with SMI were more likely to be dually eligible for Medicare and Medicaid than residents without SMI. The prevalence of SMI in AL ranged from to 3.2% in Wyoming to 33.1% in New York. Approximately 10% of AL communities had over half of the sample’s AL residents with SMI. CONCLUSIONS. Given the increased proportion of residents with SMI in AL, research is needed into the mental health and social care needs of this population. Research is needed to uncover reasons for variations across and between states.